Instilling Environmental and Disaster Awareness Through Jeneberang River School - Nurul Fatin Muhardika Mansyur; Kusuma , Kusuma; Heridadi , Heridadi; Pujo Widodo; Herlina Juni Risma Saragih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Most of the river basins in Indonesia are categorized as crisis, one of them is Jeneberang. This condition is caused by human behavior and activities that do not pay attention to environmental aspects such as the conversion of forest land into fields and there are still people who still throw their garbage into the river even though the river has a very important function for human life and livelihood. This research will focus on discussing how the Jeneberang River School instills an attitude of environmental care and disaster awareness for the community. The method used is qualitative with a descriptive design. The data was collected through interviews with the founder and principal of Sungai Jeneberang School and document/literature study. The result of this research is Jeneberang River School as a non-formal education forum that provides strengthening of knowledge and understanding related to the function of rivers and efforts to preserve them through various activities such as Focus Group Discussion (FGD), river tracing, river cleaning, tree planting, and Waste Bank socialization. Community participation in these activities is one of the keys to the effectiveness of the Jeneberang River School in instilling an attitude of environmental care and disaster awareness to the community. Based on the results of the research, it was also found that there are still some obstacles for the Jeneberang River School, namely in terms of human resources, human resources, and human resources.